Optimal microstructure and mechanical properties of open-cell porous titanium structures produced by selective laser melting - Kulcsár, Klaudia; Buzgo, Matej; Costa, Pedro Ferreira; Zsoldos, Ibolya (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract Three-dimensional printing technology enables the production of open cell porous structures. This has advantages but not only in terms of weight reduction. In implant structures, the process of osseointegration is improved, mechanical integration is better, the open cell porous structures resemble a trabecular structure that mimics bone tissue. In this work, we investigated titanium structures made porous by cutting spheres. Based on the patterns of different types of crystal models we created porosity with different strategies. We have shown that there are significant differences in mechanical properties between the porous structures formed with different strategies. We determined the structure that loses the least load-bearing capacity compared to the solid structure, with the same porosity levels and mechanical stresses. We characterized the possibility, location and environment of becoming an open cell structure. We performed the calculations with mechanical simulations, which were validated experimentally. The quality of the three-dimensional printing of samples was checked by computer tomography reconstruction analysis.